A prospective study on sexual deviation deployed in Baghdad crimes - جبار فريح شريدة (College of Education for Women, 2019)
The current research aims to identify the types and rates and the reasons for the crimes that are with the origin and sexual scattered deviation between the fabric of Iraqi society, which reticent about because of the culture of the community, where he offered a researcher investigator justice and tribal leaders and lawyers about proportion and the types and causes of crime is the origin of sexual deviance and finally a question asked a researcher in 1000 young lived their adolescence days of the former regime (1979-2003) from going to brothels researcher found that 920 people and 92% had gone to the house to practice adultery and that 70 of them, and by 7% had engaged in masturbation only and that 10 of them have not committed anything noteworthy and by 1% They have maintained themselves. It found that there are a lot of crimes reticent by the media because of the social values and traditions